Marketmakers versus matchmakers - Yavaş, Abdullah (Journal of Financial Intermediation, 1992)
This paper examines why we have marketmakers (specialists in stock markets, used-car dealers) in some markets and matchmakers (real-estate brokers, employment agencies) in others. Using a bilateral search model, it is shown that when the valuations of the agents are private information, marketmaking might yield higher or lower profits and welfare effects than matchmaking, depending on the efficiency and the cost of search and on the distribution of valuations of the agents. This is in contrast to an earlier result that when the agents' valuations are common knowledge marketmaking yields higher profits and greater welfare effects than matchmaking.